AN AR INDOOR POSITIONING SYSTEM BASED ON ANCHORS - Varelas, Thomas; Pentefoundas, Alexandros; Georgiadis, Charalabos; Kehagias, Dionysios (MATTER: International Journal of Science and Technology, 2020)
Indoor navigation is a very interesting scientific domain due to its potential use compared with the GPS signals, which are restricted to outdoor environments. This paper describes commonly used methods of Indoor navigation, positioning, and mapping systems using Augmented Reality (AR) techniques. An Indoor navigation system, which is based on an AR application, is a pipelined procedure, which is consisted of three modules. Those are the positioning system, the map, and the route planning algorithms. In this paper, the emphasis is placed on the positioning system module and the creation of the map. The most notable options concerning the AR positioning systems use markers or detected planes in the environment in order to accurately define the position of the user in it. In this paper, we propose a new method of positioning which is based on anchors and unlike other methods can provide a total marker-less experience to the user. Anchors are a crucial feature of most AR Frameworks and used to add augmented content on top of a feature point. Also, we propose a mapping technique that fully supports the positioning method mentioned previously. Concepts like AR Frameworks, anchors, and feature points are also, deeply discussed. The proposed method for position tracking does not require any special hardware or component other than a smartphone with a camera. The proposed method for map creation is an enhanced version of an existing method of the ARKit framework. Finally, the paper analyzes the new methods in terms of accuracy in the estimated user position and measures the error in a distance calculation module that was developed to support the positioning method.